Sentiment analysis towards naturalization of Indonesian National Team Players on social media x using the Naive Bayes method - Lubis, Fahrian Zibran; Kurniawan, Rakhmat (Institute of Computer Science (IOCS), 2025)
This study analyzes public sentiment toward naturalized players in the Indonesian National Team on social media platform X (formerly Twitter) using the Naïve Bayes method. Data were collected via Python's snscrape library through web crawling, encompassing 700 tweets from January 2023 to May 2024. The research methodology included data preprocessing (cleaning, case folding, tokenizing, stopword removal, and stemming), feature extraction with TF-IDF (Term Frequency-Inverse Document Frequency), and sentiment classification. Results revealed a dominant negative sentiment (87.5%) compared to positive sentiment (12.5%), with a model accuracy of 88%. The most frequent keyword,